PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING DENGAN PUZZLE TERHADAP KEMAMPUAN KOGNITIF ANAK USIA 5 - 6 TAHUN - Badri Munawwirah; Parwoto Parwoto; Sitti Nurhidayah Ilyas (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2021)
This study aims to determine whether there is an effect of the application of problem solving learning models with puzzles on the cognitive abilities of children aged 5-6 years in TK Dharma Wanita Ajakkang Timur, Barru Regency. The research approach used is a quantitative approach with the type of Quasi Experiment research. The population in this study was group B in TK Dharma Wanita Ajakkang Timur Kab. Barru. Sampling in this study was purposive sampling. The sample in this study were 10 children, 5 children as the experimental group and 5 children as the control group. The data collection technique used is descriptive statistical analysis and nonparametric statistical analysis. Based on the results of the study, it can be concluded that there is an effect of the problem solving learning model with puzzles on the cognitive abilities of children in the experimental class.